Validitas dan Kepraktisan E-Module Berbasis Phenomenon Based Learning Menggunakan Articulate Storyline pada Materi Sifat Koligatif Larutan - Abdullah; Herdini; Putri, Tiara Swastika (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce an E-Module of Colligative Properties of Phenomenon-Based Learning-Based Solutions Using the Articulate Storyline Application for 21st Century Skills Mastery. This research is a type of research and development or R&D using a 4-D model consisting of 4 stages, but this research is only only at the development stage. The results of the research carried out are in the form of electronic modules (e-modules) on colligative chemistry materials that are valid and practical. The validity aspect is determined from the validator's assessment and the practicality aspect is determined from student responses to this E-module. The results for the validity aspect of the e-module were declared very valid with a presentation of 96.667%. The research results on the practical aspect of e-modules received a very good response from teachers with a presentation of 97.188% and very good from students with a presentation of 99.44%. These results indicate that the e-module on colligative properties of solutions developed is valid and practical for use as an alternative teaching material in the learning process.